Unhastening science : autonomy and reflexivity in the social theory of knowledge - Pels, Dick, 1948- (Studies in social and political thought, 2003)
This book offers a new account of what makes science special among other human pursuits, critically engaging with a variety of approaches, especially constructivist and relativist studies of science and technology. It focuses on the studied?lack of haste? of science, its relative stress-freeness and its socially sanctioned withdrawal from the swift pace of ordinary life. Unhastening Science offers a balanced and thoughtful argument which emphasises the dangers of cosseting science from the?scourge? of internal competition while at the same time highlighting the need for?distance? between th.